The Performance of Indonesian Islamic Rural Banks During Covid-19 - Julia Noermawati Eka Satyarini; Rofiul Wahyudi; Shah Amelia Manggala Putri; Mia Rizka Tusyani (At-Taqaddum, 2022)
The Covid-19 pandemic caused turbulence in all sectors, including Islamic Rural Banks. The financial performance of Islamic Rural Banks has come under pressure due to the decline in SMEs financing quality. Therefore, this study aims to analyze the financial performance of Indonesian Islamic rural banks during the Covid-19. This research method uses a descriptive quantitative approach with secondary data in financial statements from 165 Islamic Rural Banks in Indonesia as a population and sample. Data analysis techniques use descriptive statistics to reveal the performance of Islamic Rural Banks during the Covid-19 pandemic for the January-December 2020 period, which includes Productive Asset Quality, Non- Performing Financing, Return on Assets, BOPO, Financing to Deposit Ratio, and Cash Ratio. The findings of this study show that most Islamic rural banks have experienced a decline in financial performance. The implication is that Islamic rural banks must strengthen risk management to deal with the possibility of similar or other pandemics in the future.